Pengaruh Good Corporate Governance Dan Sales Growth Terhadap Tax Avoidance - Sella Anggining Putri (2021)
This study ains to analyze the effect of the competence of the board of commissioners, the competence of audit comitte, institutional ownership, and sales growth on tax avoidance with profitability and firm size as a controlling variable. The object of this research is manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2019 period, with a total sample of 129 companies. This research uses quantitative methods using panel data. The data analysis technique used is the classical assumption test, panel data estimation selection test, multiple linear regression test, and hypothesis testing using a significance of 5%. The result of this study state that the sales growth variable has a negative significant effect on tax avoidance, while the competence of the board of commissioners, the competence of audit comitte, institusional ownership has no effect on tax avoidance. In addition, control variable namely profitability has a positive significant effect on tax avoidance and firm size has a negative significant effect on tax avoidance.